Out-of-pocket health expenditure in people with diabetes and hypertension at the first level of care in Encarnación, Paraguay - Dressler, Diana; Gimenez Caballero, Edgar (Medicina Clínica y Social, 2024)
Introduction: Out-of-pocket health spending refers to the direct expenses people make for medical services, medications, and other health care. In patients with chronic diseases, it becomes significant due to the economic burden it generates at home. Objective: Analyzing the characteristics of out-of-pocket health spending and its economic effect in the homes of people with Diabetes and Hypertension at the first level of care. Methodology: A quantitative, non-experimental, cross-sectional research. It included a non-random sample of 201 patients from the Family Health Units of the District of Encarnación, to whom a survey with a one-time measurement was applied. The dependent variables were out-of-pocket health spending, spending/income ratio, excessive health spending, and catastrophic health spending. The independent variables: Type of chronic disease and presence of complications. The significant association was determined using Chi2, Kruskal Wallis and Mann-Whitney tests (p
Keywords: Out-of-pocket spending on health; financial protection; non-communicable chronic diseases; first level of care